Molecular resistance mechanisms to newly approved antibiotics (2017–2025) in WHO priority pathogens - Sartori, M.; Toppo, S.; Lavezzo, E. (Frontiers in Microbiology, 2026)
The relentless rise of antimicrobial resistance (AMR) poses a critical threat to global public health, rendering once-effective therapies obsolete. In response, several novel antibiotics have been developed in recent years. This review systematically summarizes the molecular resistance mechanisms that World Health Organization (WHO) priority bacterial pathogens have already deployed against the 15 new antibiotics approved between 2017 and 2025, including β-lactam/β-lactamase inhibitors (cefiderocol, ceftazidime-avibactam, meropenem-vaborbactam), tetracycline derivatives (eravacycline, omadacycline), a pleuromutilin (lefamulin), an aminoglycoside (plazomicin), and a fluoroquinolone (delafloxacin). We detail how pathogens utilize four primary strategies to overcome these last-line agents: enzymatic inactivation (e.g., by KPC, NDM, OXA-48, and Tet(X) variants), efflux pump overexpression (e.g., AdeABC, AcrAB-TolC, MexAB-OprM), modifications of target sites (e.g., PBP3, RpoB, ribosomal proteins/L3, and QRDR mutations), and reduced membrane permeability. Evidence consistently demonstrates that resistance emerges rapidly, often through pre-existing genetic pathways repurposed against the new chemical structures. This analysis underscores the paradoxical reality of antimicrobial development: the introduction of new therapies simultaneously selects for and elucidates new resistance mechanisms. Preserving the efficacy of these essential drugs thus necessitates a multifaceted, globally coordinated “One Health” strategy. Finally, we discuss how the growing complexity of AMR mechanisms is driving the need for advanced diagnostic tools, exploring the pivotal role of bioinformatics and artificial intelligence in predicting resistance and closing knowledge gaps.